Characteristics and Outcomes Among Patients With Autoimmune Rheumatic Diseases Requiring a Higher Level of Care. Issue 7 (October 2021) - Parperis, Konstantinos; Al-Charakh, Mohammed; Nzuonkwelle, Sumediah; McPherson, Mark; Al-Marzooq, Ali; Bhattarai, Bikash
Abstract : Objective: Patients with autoimmune rheumatic diseases (ARDs) have a higher risk of developing organ failure, and they may require admission to the intensive care unit (ICU). The aim of our study is to determine the reasons for admission to the ICU, identify potential risk factors associated with mortality, and assess the outcomes of patients with ARD diseases admitted to the ICU. Methods: We conducted a medical records review study of patients with ARD admitted to the ICU from 2012 to 2018. Patient data included demographic and clinical characteristics, ICU admission diagnoses, length of stay, complications, and immunosuppressive regimen. Short-term and long-term outcomes were assessed. Results: A total of 80 ARD patients were identified with the mean age of 48.8, 67% were female, and 56% were Hispanic. The most common disease associated with ICU admission was systemic lupus erythematosus (42%), followed by rheumatoid arthritis (26%), and 12% of patients had systemic vasculitis. Sepsis was the leading cause of ICU admission, accounting for 31%, followed by respiratory failure due to pneumonia (10%) and congestive heart failure (10%). Twenty percent of patients died in the ICU, 5% died 30 days after ICU admission, and 7.5% died within 1 year after the ICU stay, resulting in overall mortality of 33% by the end of 1 year. Nonsurvivors were more likely to need mechanical ventilation ( p = 0.001), vasopressor support ( p < 0.001), had renal ( p = 0.041) or cardiovascular ( p < 0.001) involvement on admission, APACHE II score higher than 19 ( p = 0.001), and 4 days or longer stay in the ICU ( p = 0.001). Conclusions: Our findings indicated that systemic lupus erythematosus is the most common ARD associated with ICU admission, and sepsis was the most frequent cause. Predictors associated with higher mortality were the requirement for mechanical ventilation, vasopressor support, increase length of ICU stay, and renal and cardiovascular involvement on admission.